1959
DOI: 10.1126/science.130.3369.217-a
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Conditioning of Lemon Sharks

Abstract: Two sharks were trained to feed at a target which, when pressed, caused a submerged bell to ring. Later they were trained to press the target for remotely placed food. They retained this conditioned response after a 10-week period of inactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 3 publications
3
35
0
Order By: Relevance
“…Shovelnose rays, G. typus, successfully performed a four-choice discrimination task, which confirms earlier work showing that elasmobranchs are capable of learning visual discrimination tasks (Clark, 1959;Clark, 1963;Wright and Jackson, 1964;Tester and Kato, 1966;Hodson, 2000). The rays were capable of discriminating coloured reward stimuli from differently coloured distracter stimuli that varied in relative brightness from trial to trial.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Shovelnose rays, G. typus, successfully performed a four-choice discrimination task, which confirms earlier work showing that elasmobranchs are capable of learning visual discrimination tasks (Clark, 1959;Clark, 1963;Wright and Jackson, 1964;Tester and Kato, 1966;Hodson, 2000). The rays were capable of discriminating coloured reward stimuli from differently coloured distracter stimuli that varied in relative brightness from trial to trial.…”
Section: Discussionsupporting
confidence: 75%
“…The earliest behavioural experiments on sharks concentrated on demonstrating that sharks were capable of being conditioned to press a target in order to receive a food reward (Clark, 1959;Wright and Jackson, 1964;Aronson et al, 1967). From these studies, more complex behavioural experiments that examined shape recognition and colour vision were developed.…”
Section: Introductionmentioning
confidence: 99%
“…Although conditioning was successful with only the visual stimulus, they found that the success rate was significantly greater with the addition of sound reinforcement. As with Clark (1959) Fig.4. Opcrant conditioning of a young nursc shark.…”
Section: Captive Behaviour and Operant Conditioningmentioning
confidence: 57%
“…Once acquired, there was a long retention period for this behaviour. Even after a lapse of 10 weeks, sharks quickly pressed the target (Clark, 1959). There was some evidence that they learned to associate the ringing of a bell with food delivery as well.…”
Section: Captive Behaviour and Operant Conditioningmentioning
confidence: 95%
See 1 more Smart Citation